SEMIOTICS ANALYSIS OF GENDER STEREOTYPE IN “DOVE” SHAMPOO PRODUCT ADVERTISING: ROLAND BARTHES’ SEMIOTICS APPROACH - Irfan Hanify Salim (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2023)
This study aims to analyze how stereotypes of women are represented in Dove shampoo advertisements and to analyze the semiotics of gender stereotypes in “Dove” shampoo product advertising using Roland Barthes’ semiotics approach. This study uses a qualitative method by taking primary data sourced from online media ‘YouTube’. The data source is in the form of advertisements for Dove shampoo products in 2022. The advertisement entitled “My Hair is My Crown (Rambutku Mahkotaku) - Dian Sastrowardoyo & Other Women’s Stories About HairBullying”. While the data analysis technique in this study was carried out by identifying signs according to the stages proposed by Roland Barthes (Roland Barthes’ semiotic theory) to determine the meaning of denotation and connotation of advertisements. The results of this study indicate that Dove shampoo advertisement analysis using the Barthes analysis model approach can be explained based on the analysis model by looking at the meaning of denotation and connotation. 5 hairstyles become the outline of the text that strengthens the purpose of depicting the ad including how the woman in the ad is depicted. In addition, each of the women with the 5 hairstyles had experienced hair-bullying because it did not fit the stereotypes of the society (Indonesian people). The five hairstyles are (1) straight hair (just straight), (2) short hair, (3) honeycomb hair, (4) colored hair, and (5) hijab. However, through the shampoo advertisement, Dove wanted to raise awareness about hair-bullying that women often face, through an anti-bullying song titled “My Hair is my Crown (Rambutku Mahkotaku)”. In more detail, Dove wanted to maintain women’s confidence in how to choose and express their hair and break down societal views and stereotypes about what is often considered “beautiful hair”.